جريمة االعتداء على حرمة الحياة الخاصة عبر وسائل اإلعالم دراسة فقهية مقارنة بالقانون الوضعي بحث مستل من أطروحة دكتوراه في الشريعة اإلسالمية - كريم, فاروق عبداهلل; عثمان, ئاراس حمه أمين (Sulaimani Journal for Humanities, 2022)
The Media freedom is a natural right for every person in Islam and in all monotheistic religions and man-made laws, it is the best way through which the person can express his own opinions, criticize, observe and state on various matters. There is no doubt that the modern media have a great advantage in developing methods of expressing opinion, which led to the development of ideas and information and the convergence of different points of view. It exceeded the emergence of negative matters such as committing crimes and violating to the rights and freedoms of others through these means under the freedom of expression, the press and the media. One of those transgressions that pose a serious threat to the lives of individuals in human society is the crime of assaulting and exposing private life to appearance, and publishing the secrets of others through the media, which are prohibited by Islam, as criminalized by international and local legislation and laws.